Ilmu dan Guru di Zaman Nabi Muhammad SAW - Wagiman Manik (Intiqad: Jurnal Agama dan Pendidikan Islam, 2020)
Islam is built on knowledge and charity, without knowledge a charity will not be acceptable and it could be that the practice is invalid. Therefore, Islam requires all adherents and adherents, both men and women to study. In addition to being an obligation, it is an obligation to seek knowledge, it turns out that Islam provides and prepares great rewards for those who are diligent and sincere in pursuing this knowledge. The virtue of knowledge and experts is very clear in this glorious Islamic religion, that knowledge is the cause of the easy path for a person to go to heaven.Truly all the friends ra. are teachers, because this noble religion came to us thanks to their tenacity and sincerity in conveying and teaching Islam to humans. The companions of the Prophet Muhammad are the best teachers in Islam after the Prophet Muhammad, because they have very good, praiseworthy and noble traits, character and characteristics. Therefore, every Muslim and Muslim educator should be able to follow, imitate and emulate the characteristics in their daily educational activities, even though sometimes there are some educators who are unable to make it happen optimally, but of course they still have to try their hardest to emulate the characteristics of these friends.